Analysis Of Students' Arabic Speech Rhythm In Mataram State Islamic University - Abdul Azis Azis; Moh Nasikin (The Center for Language Development, Mataram State Islamic University., 2024)
This paper seeks to explain how students enrolled in the Arabic Language Study Programme at the State Islamic University of Mataram acquire Arabic speech rhythm. The research method utilised was a quantitative descriptive method termed as a survey study which covered 91 respondents comprising of 45% males and 55% females and consisting of the 2020 (40%), 2021 (35%) and 2022 (25%). The findings indicated that around 15% of the respondents are found to be very excellent in the mastery of Arabic rhythms, 40% moderate, 30% poor mastery while 15% did not master Arabic rhythms at all. Other than the place of residence, the factors that contribute to the mastery of speech rhythm are educational background, training frequency and exposure to Arabic-language media where the respondents cited all three as contributing factors totalling 100%, with how many percent each contributing further indicating language barriers such as 40%, 35%, and 25% respectively. Bilingualism is crucial for pronunciation; however, students pointed out their inability to acquire accurate bilingualism as one of the reasons for the students’ deficient Arabic pronunciation, which also involves difficulties in controlling the tempo of pronunciation (50%), the syllables during pronunciation (30%), and acquiring an Arabic vocabulary (20%). Students wish for special training (45%), using audio/video learning media (30%), and receiving individual supervision (25%) in order to better their control of the speech rhythm. The study states that even though a reasonable number of students have acquired sufficient control of rhythm, a great number still have problems with controlling the appropriate timing and pressure when speaking. This calls for more natural and rhythmic Arabic speaking through more practical exercises and accompanying media.